Peer Review of Teaching and the TEF – We Need More than a Tick-Box Exercise to Improve the Quality of Teaching - Marty Chamberlain (London School of Economics Social Science Impact Blog, 2015)
This blog for the LSE critically discusses the implementation of the TEF in relation to the training of academic staff and individualist vs collectivist conceptions of teaching quality.